Trade Liberalization and Investment in Foreign Capital Goods : A Look at the Intensive Margin - Kandilov, Ivan T. (Taylor and Francis, 2022)
We evaluate the impact of trade liberalization on the intensive margin of the firm’s investment in foreign capital goods. To do so, we use Indian firm-level panel data from a period of a large-scale trade liberalization (1989–1997) to estimate an investment equation using the system-GMM estimator. Importantly, we control separately for the tariffs on capital goods, intermediate inputs and final goods, which allows us to estimate the price elasticity of investment in foreign capital goods. Consistent with theory, we find that reductions in the tariffs on capital goods, and intermediate inputs led to higher investment in foreign capital goods, whereas reduction in the output tariff resulted in lower investment. The impact of the capital goods tariffs is the largest.